Derivative Estimates for the Solution of Hyperbolic Affine Sphere Equation (Communications in Mathematical Research, 2021)
Considering the hyperbolic affine sphere equation in a smooth strictlyconvex bounded domain with zero boundary values, the sharp derivative estimates ofany order for its convex solution are obtained.